Pattern of Complementary Feeding among Mothers Having Child Aged 6 to 12 Months - Haque, Md Monoarul; Nahar, Nurun; Prodhania, Md Shafiullah; Lima, Farzana Rahman; Bhuiyan, Md Rijwan; Hossain, SM Azmol (Delta Medical College Journal, 2016)
Background: Infant feeding practices play a crucial role in determining a childs rate of growth and development. Improper feeding practices have not only continued to jeopardize the nutritional status of Bangladeshi Children but also the well being of millions of children all over the world. Objective: The aim of the study was to assess pattern of complementary feeding among mothers having child aged 6 to 12 months. Materials and method: This was a cross sectional study conducted among 125 mothers having child aged 6 to 12 months. Purposive sampling method was used and pretested structured questionnaire was used to collect data by face to face interview. Prior data collection verbal consent was taken from respondents. Results: Mean age of the infants was 9.95±2.046 months. Maximum 24% of the mothers were educated up to class VI-IX. About 47.2% mother introduced complementary feeding at 6th month to their infants. Among the age group of 6 to 8 months 13.9%, 44.4%, 30.6% and 11.1% children received meal for 1-2 times/day, 3-4 times/day, 5-6 times/day and more than 6 times/day respectively. In 6-8 months age group 52.8%, 19.4%, 16.7%, 8.3% and 2.8% were given semi solid and liquid, semi solid and solid, liquid, semi solid, and solid respectively. Besides 64% respondents gave Rice/Rice Powder/Suzy as complementary feeding, 60% received khichuri, and 4.85% gave non-infant formulae. Conclusion: Overall pattern of complementary feeding was not satisfactory. Further large scale study is needed to get actual picture. Delta Med Col J. Jan 2016 4(1): 13-17